2007
DOI: 10.1128/jb.00161-07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions of DNA Repair Pathways in the PathogenNeisseria meningitidis

Abstract: The current increase in the incidence and severity of infectious diseases mandates improved understanding of the basic biology and DNA repair profiles of virulent microbes. In our studies of the major pathogen and model organism Neisseria meningitidis, we constructed a panel of mutants inactivating genes involved in base excision repair, mismatch repair, nucleotide excision repair (NER), translesion synthesis, and recombinational repair pathways. The highest spontaneous mutation frequency among the N. meningit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
4
32
0
Order By: Relevance
“…Thus, the effect of lowering RecA expression in wild-type cells or uvrABC mutants has a relatively minor effect on UV survival. This is similar to the effect reported by Davidsen et al in a uvrA recA6 double mutant from the related human pathogen Neisseria meningitidis (11). Intriguingly, we observed a large increase in UV sensitivity in the mfd mutant in the absence of RecA expression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, the effect of lowering RecA expression in wild-type cells or uvrABC mutants has a relatively minor effect on UV survival. This is similar to the effect reported by Davidsen et al in a uvrA recA6 double mutant from the related human pathogen Neisseria meningitidis (11). Intriguingly, we observed a large increase in UV sensitivity in the mfd mutant in the absence of RecA expression.…”
Section: Discussionsupporting
confidence: 78%
“…In 1997, Black et al demonstrated that the Gc uvrA gene could complement an E. coli uvrA mutant for UV survival (3), and in 1995 the same group demonstrated that a uvrB mutant was deficient in UV survival (4). Finally, Davidsen et al demonstrated that a Neisseria meningitidis uvrA mutant was also deficient for UV survival but not altered for survival to alkylating agents (11). The involvement of NER in other DNA recombination and repair pathways in pathogenic Neisseria, such as natural competence, repair of spontaneous mutations, and pilus variations, has not been defined.…”
mentioning
confidence: 99%
“…In E. coli, MMC mutants exhibit a striking increase in the frequency of spontaneous mutation to antibiotic resistance (reviewed in reference 3), whereas the increase in mutation frequency to Nal r in MMCdeficient Gc was only 4-to 5-fold above the parental strain. This observation is in agreement with the effects of MMC inactivation in N. meningitidis (7,26,38). While in E. coli uvrD (also termed mutU) and mutS/L mutants have similar effects on spontaneous mutation (28), in Gc the mutation frequency in uvrD MMC double mutants is significantly higher than any single mutant.…”
Section: Discussionsupporting
confidence: 77%
“…2). Similar low increases in the frequency of spontaneous mutation have previously been reported for mutS and mutL mutants in N. meningitidis (7,26,38). Therefore, mutS and mutL are functional MMC genes in Gc and have modest effects on the correction of point mutations in this organism.…”
Section: Identification and Mutagenesis Of MMC Genes In Gcsupporting
confidence: 55%
“…Previous studies have shown that UV-induced DNA damage is repaired mostly by nucleotide excision repair in N. meningitidis (Davidsen et al, 2007). However, cells lacking RecA .…”
Section: Dpra Is Dispensable For Dna Repair Following Uv Mutagenesismentioning
confidence: 99%